Response and damping of a rectangular cantilever plate with vibrating beam dampers - Arpaci, A.; Savci, M. (Elsevier BV, 1986)
Abstract In this work the use of beams as auxiliary mass dampers for cantilever plates is considered. Because the cantilever plate problem, which is of strong industrial interest, does not lend itself to a Levy-type solution, the procedure developed by Ritz is used. Structural damping is incorporated into the main and auxiliary systems by treating them as having a complex elastic modulus. With appropriate selection of the parameters, the fundamental resonance of the plate is split into two new ones with considerably suppressed responses. In order to verify the analysis, an experimental investigation was carried out and the results obtained were compared with the theory developed.